Adaptive control for manipulators with unknown virtual control coefficients and input nonlinearities. Issue 11 (14th April 2022) - Zhou, Tianyue; Liu, Cungen; Wang, Huanqing; Sun, Yulong; Ma, Piming; Zhang, Wensheng; Zhu, Weihong
Abstract: This paper addresses the adaptive control problem for a one‐link manipulator system driven by a motor with uncertain virtual control coefficients (VCCs) and nonlinearities. The unknown VCCs are composed by the certain and uncertain items, where the first part is decided by the moment of inertia of the manipulator and another is generated by that of the load. An auxiliary variable and the Nussbaum gain technique are invoked to handle the uncertainties of VCCs and input nonlinearities. Moreover, a finite‐time prescribed performance function is introduced to design the adaptive control scheme for the manipulator system, which guarantees the tracking error converges to a fixed interval in a setting time and all signals in the manipulator system are bounded.